2010
DOI: 10.1007/s00580-010-1079-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma thyroid hormones and some biochemical parameters in Iranian Sarabi calves

Abstract: The thyroid gland has some important endocrine hormones that regulate basal metabolism in various tissues of domestic animals. Thyroid hormones have a central role in animals' development and their tissue functions. In this study, the relationship between the plasma thyroxine (T 4 ), triiodothyronine (T 3 ), free thyroxine (fT 4 ), free triiodothyronine (fT 3 ), triglyceride, cholesterol, glucose, total protein, and albumin concentrations as well as albumin/globulin ratio in different ages of Iranian Sarabi ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Latour et al (1996)mentioned that the observed changes suggest that many of the physiological and biochemical processes function differently in embryos from parents of different ages, a large proportion remains un used up to hatch and becomes sequestered into the body cavity and under appropriate conditions is utilized by 5days post hatch. The results of significant increase of plasma globulin for baby chicks produced from younger flock could be due to the increase of globulin concentration of parent flock at 32-42wk of age as younger age as confirmed by Eshratkhah et al (2011) who found significant increase in serum globulin at 32-34 weeks of old. From our point of view, we can refer that this increase of globulin concentration in blood of baby chicks for younger flock could be related to the increase of OPN either in the blood of mothers or from their eggshells as previously detected in Table 1.…”
Section: Blood Parametersmentioning
confidence: 70%
See 1 more Smart Citation
“…Latour et al (1996)mentioned that the observed changes suggest that many of the physiological and biochemical processes function differently in embryos from parents of different ages, a large proportion remains un used up to hatch and becomes sequestered into the body cavity and under appropriate conditions is utilized by 5days post hatch. The results of significant increase of plasma globulin for baby chicks produced from younger flock could be due to the increase of globulin concentration of parent flock at 32-42wk of age as younger age as confirmed by Eshratkhah et al (2011) who found significant increase in serum globulin at 32-34 weeks of old. From our point of view, we can refer that this increase of globulin concentration in blood of baby chicks for younger flock could be related to the increase of OPN either in the blood of mothers or from their eggshells as previously detected in Table 1.…”
Section: Blood Parametersmentioning
confidence: 70%
“…Also, Hocking et al (2001) found that a decline in calcium and phosphorus content in eggshell due to age of hen. In addition, breeder hen age affects plasma cholesterol, total lipids, globulin, and glucose levels for newly hatched chicks as mentioned by Latour et al (1998) and Eshratkhah et al (2011). Asymmetry refers to the random deviations from symmetry in the development of bilaterally symmetrical traits, fluctuating asymmetry, deviating in either direction with a normal distribution and a mean of zero (Moller, 1990).…”
Section: Introductionmentioning
confidence: 99%